2018
DOI: 10.1039/c7qm00385d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible colour changes of mixed films composed of 4,4′-bis[bis(4-methylphenyl)amino]azobenzene and organic acids in response to exhaled breath

Abstract: Mixed films of the title aminoazobenzene with a few different conventional organic acids exhibited drastic and reversible colour changes when exposed to exhaled breath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It was speculated that this result was due to the high water content. Nakano et al reported that H 2 O in breath caused deprotonation, and the blue‐shift (from the protonated state to the deprotonated state) was observed 53 . Therefore, we supposed that protonated state could be highly sensitive to H 2 O, and N_fluo did not show red‐shift in the case of HCl and HBr.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…It was speculated that this result was due to the high water content. Nakano et al reported that H 2 O in breath caused deprotonation, and the blue‐shift (from the protonated state to the deprotonated state) was observed 53 . Therefore, we supposed that protonated state could be highly sensitive to H 2 O, and N_fluo did not show red‐shift in the case of HCl and HBr.…”
Section: Resultsmentioning
confidence: 79%
“…Nakano et al reported that H 2 O in breath caused deprotonation, and the blue-shift (from the protonated state to the deprotonated state) was observed. 53 Therefore, we supposed that protonated state could be highly sensitive to H 2 O, and N_fluo did not show red-shift in the case of HCl and HBr. These data represent that the type of acids can discriminate by selecting the aza-substitution manner at the main-chain conjugation.…”
Section: Resultsmentioning
confidence: 92%
“…We have designed and synthesized of a novel molecule, BFBZA, and found that the hybrid amorphous film of BFBZA with BA exhibited reversible change in emission color in response to exhaled breath whereas BFBZA-PFBA film did not change the emission color. In our previous paper [21,23], acidity levels of organic acids were the important factor for providing hybrid films that exhibit reversible changes in object colors and emission colors in response to moisture. The present study suggested that the basicity level of emitting material was also the important factors, that is, the balance of acidity level of organic acid and basicity level of emitting amorphous molecular materials plays a role for exhibiting reversible change in emission color.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have reported that spincoated films of diarylaminobenzaldehyde-based emitting amorphous molecular materials exhibited vapochromic emission [11]. In addition to such materials with single component systems, we have recently been studying the creation of hybrid systems of amorphous molecular materials with other materials exhibiting smart functions [13][14][15][16][17][18][19][20][21][22][23]. We have reported that the hybrid films of aminoazobenzene-based amorphous molecular materials with organic acids exhibited drastic and reversible color changes in response to moisture [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrochromic materials have a broad spectrum of applications, (Park et al 2016b;Ni et al 2019) such as breath detection, air humidity detection, (Zhou et al 2021) anticounterfeiting encryption inks, (Kou et al 2018) water content sensors, (Karimipour et al 2020;Sun et al 2021) rewritable papers (Mao et al 2021), and human sweat pore mapping technologies. (Kitamura et al 2018) Hydrochromic materials include graphene oxide, (Chi et al 2021) triarylmethane proton transfer, (Jiang et al 2021) metal salt with crystal water, photonic crystals (PCs), (Jung et al 2021) polydiacetylenes (PDAs), cholesteric liquid crystals, (Stumpel et al 2015;Meng et al 2020;Momtaz and Chen 2020;Yoo et al 2020) lanthanide-ion-coordinated supramolecular hydrogel (Yao et al 2020), aggregation-induced-emission (AIE) molecular, (Jiang et al 2021) and covalent organic framework (Kitamura et al 2018).…”
Section: Introductionmentioning
confidence: 99%